Outcome of pregnancies with recent primary cytomegalovirus infection in first trimester treated with hyperimmunoglobulin: observational study. (17th March 2021) - Kagan, K. O.; Enders, M.; Hoopmann, M.; Geipel, A.; Simonini, C.; Berg, C.; Gottschalk, I.; Faschingbauer, F.; Schneider, M. O.; Ganzenmueller, T.; Hamprecht, K.
ABSTRACT: Objective: To examine the efficacy of hyperimmunoglobulin (HIG) treatment in women with a recent primary cytomegalovirus (CMV) infection up to 14 weeks' gestation. Methods: This is an ongoing observational study conducted at the prenatal medicine departments of the University Hospitals of Tübingen, Bonn, Cologne and Erlangen, Germany, as well as at the Laboratory Prof. Gisela Enders and Colleagues in Stuttgart, Germany and the Institute for Medical Virology at the University of Tübingen, Tübingen, Germany. Enrolment criteria were the presence of confirmed recent primary CMV infection in the first trimester and a gestational age at first HIG administration of ≤ 14 weeks. The following inclusion criteria indicated a recent primary infection: low anti‐immunoglobulin (Ig)‐G levels, low anti‐CMV‐IgG avidity in the presence of a positive CMV‐IgM test and no positive reactivity or just seroconversion anti‐gB2‐IgG‐reactivity. HIG administration was started as soon as possible within a few days after the first visit. HIG was administered intravenously at a dose of 200 IU/kg maternal body weight and repeated every 2 weeks until about 18 weeks' gestation. The primary outcome was maternal–fetal transmission at the time of amniocentesis. Multivariate logistic regression analysis was used to determine significant covariates that could predict maternal–fetal transmission. Results: We included 149 pregnancies (153 fetuses) that completed the treatment. Median maternal age and weight were 32.0 years and 65.0 kg, respectively. Median gestational age at the time of first referral to one of the four centers was 9.4 weeks. Median anti‐CMV‐IgG level, anti‐CMV‐IgM index and CMV‐IgG avidity were 5.7 U/mL, 2.5 and 22.3%, respectively. HIG treatment was started at a median gestational age of 10.6 weeks and ended at a median of 17.9 weeks. Within this time frame, HIG was administered on average four times in each patient. Amniocentesis was carried out at a median gestational age of 20.4 weeks. In 143 (93.5%) of the 153 cases, the fetus was not infected. Maternal–fetal transmission occurred in 10 cases (6.5% (95% CI, 3.2–11.7%)). On uni‐ and multivariate logistic regression analysis, the level of anti‐IgM index was the only factor associated significantly with maternal–fetal transmission at amniocentesis. However, only four (40.0%) of the 10 cases with maternal–fetal transmission had an anti‐IgM index above 11.4, which corresponds to the 95 th centile of pregnancies without transmission. Conclusions: HIG is a treatment option to prevent maternal–fetal transmission in pregnancy with a primary CMV infection. However, HIG treatment seems to be beneficial primarily in women with a recent primary infection in the first trimester or during the periconceptional period, and when it is administered at a biweekly dose of 200 IU/kg. © 2021 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.